2009
DOI: 10.1111/j.1469-8749.2008.03264.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and tolerability of 4‐monthly versus yearly botulinum toxin type A treatment for lower‐limb spasticity in children with cerebral palsy

Abstract: In this study, we compared the long‐term efficacy and tolerability of two dosage regimens of the potent botulinum toxin type A (BoNT‐A; Dysport; Ipsen Ltd, Slough, UK) in children with cerebral palsy (CP) and lower‐limb spasticity. Children aged 1 to 8 years with diplegic CP who were able to walk (aided or unaided) were randomized (1:1) to 30 LD50 units/kg total body weight of BoNT‐A (injected into gastrocnemius muscles) every 4 months or once yearly for 2 years in this multicentre, assessor‐blinded, parallel‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
3
29
0
4
Order By: Relevance
“…Additionally, there is a study in patients with upper limb spasticity that revealed no neutralizing antibodies following injections of IncobotulinumtoxinA or a placebo [112]. Approximately 1% of 1080 subjects from an IncobotulinumtoxinA development program presented with neutralizing antibodies; however, each of the patients had been previously exposed to BoNT which contained complexing proteins [22].…”
Section: Immunogenicitymentioning
confidence: 99%
“…Additionally, there is a study in patients with upper limb spasticity that revealed no neutralizing antibodies following injections of IncobotulinumtoxinA or a placebo [112]. Approximately 1% of 1080 subjects from an IncobotulinumtoxinA development program presented with neutralizing antibodies; however, each of the patients had been previously exposed to BoNT which contained complexing proteins [22].…”
Section: Immunogenicitymentioning
confidence: 99%
“…Adultos (desde los 40 kilos): hasta 2.000 unidades 5,7,8,13,16,17,[43][44][45][46][47][48][49][50] .…”
Section: Se Recomiendaunclassified
“…In contrast to the consensus and evidence about dose, no consensus and little evidence exists about injection frequency for spastic equinus in children with CP. In the only injection frequency randomized clinical trials published to date, Kanovský et al were unable to detect a significant difference between 12‐monthly and 4‐monthly injections over a 2‐year period. This was a large study with well‐accepted outcome measures, including ankle dorsiflexion by standard goniometry and the Gross Motor Function Measure …”
mentioning
confidence: 98%
“…An essential part of the scientific method is to replicate novel studies. The primary aim of this study was therefore to investigate the optimal frequency of BoNT‐A injections for the treatment of spastic equinus, using similar injection regimens but with different outcome measures …”
mentioning
confidence: 99%
See 1 more Smart Citation